Conjunctival and intraocular swabs for the microbiological assessment of donor corneas. (6th July 2015) - Fuest, Matthias; Plum, Wolfgang; Salla, Sabine; Walter, Peter; Hermel, Martin
Abstract: Purpose: In this study, we investigated the associations between conjunctival (co) and intraocular (io) swabs and their implications for the contamination rates of organ‐cultured corneas. Methods: A total of 4177 swabs from 1054 corneas of 527 donors were acquired from the conjunctiva, after disinfection with 5% polyvinylpyrrolidone–iodine solution, and also from the anterior chamber after corneoscleral trepanation (io). Samples were incubated at 22.5 ± 2.5°C and 32.5 ± 2.5°C in thioglycollate broth for 14 days. Donor corneas were cultured in a closed system at 31°C. Microbial differentiation was performed for positive cultures. Results: A higher temperature (32.5°C) and the intraocular swab retrieving localization led to significantly higher swab positive rates (32.5°C versus 22.5°C, odds 1.65, p  <  0.0001; io versus co, odds 1, 53, p  <  0.0001). Death‐to‐collection time and laterality (left or right eye) had no significant influence on swab positivity. The cause of death significantly influenced the positive rates (p < 0.0001). Detection at 32.5°C occurred significantly earlier than at 22.5°C (p  <  0.0001). The overall comparison of detected species showed no significant differences in the variety between intraocular and conjunctival swabs. During the study period, six contaminations of organ‐cultured corneas occurred: four times Pseudomonas aeruginosa and once each Candida albicans and Staphylococcus hominis were found. Swap results and cornea contaminations were not significantly correlated. Conclusions: Co and io swabs show high microbial colonization rates, even after standard disinfection. Io swabs generally reproduce the co microbial range, most likely due to a mobilization and diversion of microorganisms during the trepanation procedure. Swab results do not yield a valuable tool to predict contaminations of organ‐cultured corneas.